Optimization of Asset-Based Community Potential in the Prayer House and Qur’an House in Tarai Bangun Village, Riau - As Sa'diah, Nur Halimah; Az Zahra Nur Fadila; Lubis, Mikyal Nabila; Selsha Amalia; Panggabean, Septina Hafy Safitri; Nasution, Suci Jilianti (As-sunnah: Jurnal Pengabdian Masyarakat, 2025)
Riau is a province that pays quite a lot of attention to the spread of religious knowledge, but there is a prayer house and a Quran house whose productivity has declined due to the lack of interest and motivation of the local community in organizing activities or training that can develop the community's potential. Therefore, the aim of the KKNT activity is to optimize the prayer house and Qur'an house, provide examples of training and various activities, and appoint cadres to continue the activities and their modules. This research uses the Asset-Based Community Development (ABCD) approach, collaborating with communities and society, discussing openly, preparing activity schedules and following up on each activity. So that during one month of KKNT activities, achievements have been realized in the form of; increasing the ability to read the Qur'an among mothers and children, the presence of new cadres who are ready to continue the tahsin program, increasing togetherness and social concern in the community, and the creation of useful handicraft products.